1992
DOI: 10.1103/physrevb.46.4978
|View full text |Cite
|
Sign up to set email alerts
|

Power-law localization at the metal-insulator transition by a quasiperiodic potential in one dimension

Abstract: The localization properties of an electron in the tight-binding potential A, cos(man ), where 0 & v & 1, are investigated. Wave functions approaching the metal-insulator transition (MIT} A. , =2 -~E ( (or the mobility edges E, =+~2 -iL~) from the metallic region are found to localize with multiple well-separated power-law decaying peaks, contradicting previous conclusions obtained with the help of the Lyapunov exponent. The general expectation of exponential localization with divergent localization length at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 31 publications
2
26
0
Order By: Relevance
“…Further, it has been shown that there is a localization-delocalization transition at a critical value of the degree of correlations imposed on the disorder in the system, and later works extended these results to other models [9][10][11][12]. Also, this type of transition can be found in quasiperiodic systems, as the Aubrey-Andre model and other models [13], indicating the importance of some type of ordering. These theoretical findings are supported also by experimental results showing delocalization and electronic transport driven by extended states in correlateddisordered GaAs=Ga 0:7 Al 0:3 superlattices [14].…”
mentioning
confidence: 80%
“…Further, it has been shown that there is a localization-delocalization transition at a critical value of the degree of correlations imposed on the disorder in the system, and later works extended these results to other models [9][10][11][12]. Also, this type of transition can be found in quasiperiodic systems, as the Aubrey-Andre model and other models [13], indicating the importance of some type of ordering. These theoretical findings are supported also by experimental results showing delocalization and electronic transport driven by extended states in correlateddisordered GaAs=Ga 0:7 Al 0:3 superlattices [14].…”
mentioning
confidence: 80%
“…As we can see, the generalized localization points (q, S , , ) of the ensemble are arranged along a reference curve that corresponds to the decay form f ( p ) = (1 + p)-'. Therefore, we expect a power-law decay of the wave function peaks, which was graphically demonstrated in [20]. We would like to mention here that the power-law localization in the extended range of the wave functions has an important effect on the conductance of the system.…”
Section: Multiplicative Superstructuresmentioning
confidence: 84%
“…In previous articles [18][19][20], we demonstrated that the characterization of one-particle states by the quantities ( q , S f , , ) gives meaningful results for the structure or shape of the wave function. As we will see in numerical applications, in some cases, most information about a given physical system is contained rather in the set { ( q p , S$)} of an appropriate ensemble of states {Ip)} .…”
Section: (8)mentioning
confidence: 98%
“…Lyapunov exponents of the form (4) as well as (5) are completely adequate choices for the study of localization phenomena only if exponential localization of the electrons is expected. When the electronic states exhibit a more complicated behaviour (like power-law localization) other forms of localization length may be opportunely used to characterize the shape of the electronic wavefunctions [13,15]. The primary aim of this work, however, was to ascertain whether the states beyond the second-order mobility edge were exponentially localized or not and the Lyapunov exponent (4) is a sensitive enough indicator for this purpose.…”
Section: Localization Lengthmentioning
confidence: 99%
“…Analytical calculations are greatly simplified by truncating the expansion of the inverse localization length to the second-order term; the main drawback of this choice is that it leaves open the question of the true nature of the states of the 'extended' phase. In fact, a vanishing second-order inverse localization length can be related to various physical phenomena: it can indicate that the electronic states are completely delocalized, but it can also be a sign that the states of the extended phase undergo a power-law localization (evidence for a behaviour of this kind, for instance, has been found at the mobility edge in specific quasi-periodic systems [13]). Finally, the inverse localization length may be non-zero even if its second-order part vanishes, in which case the 'extended' states would still be exponentially localized, although on a much larger spatial scale than that characterizing the states of the 'localized' phase.…”
Section: Introductionmentioning
confidence: 99%